2021
DOI: 10.18517/ijaseit.11.2.14143
|View full text |Cite
|
Sign up to set email alerts
|

Automated Identification Model of Ground-Glass Opacity in CT-Scan Image by COVID-19

Abstract: Ground-Glass Opacity (GGO) is an object found in the thorax due to infection. This object interferes with the normal function of the thorax in breathing. The characteristic of GGO has slightly lighter turbidity compared to normal thorax tissue on radiological images, so it is very difficult to identify it precisely. This study aims to identify the GGO pattern and find the exact area of the CT-scan image of COVID-19 sufferers. The data tested were 34 images from 34 different patients. The image was taken using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…The results of the study of Mamatha Reddy D. Cozzi et al (2021) [42] are in line with this finding of the present study in such a way that the results of their study showed that: before the start of general vaccination against COVID-19, most hospitalized patients had ground-glass opacities (GGO) on CT, but after the vaccination, GGO results decreased. Also, the results of the study of Jufriadif Na'am et al [43] (2021) are in line with this finding of the present study in such a way that the results of their study showed that: before the start of general vaccination against COVID-19, most hospitalized patients had radiology results showing ground glass opacity (GGO) in their thorax.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study of Mamatha Reddy D. Cozzi et al (2021) [42] are in line with this finding of the present study in such a way that the results of their study showed that: before the start of general vaccination against COVID-19, most hospitalized patients had ground-glass opacities (GGO) on CT, but after the vaccination, GGO results decreased. Also, the results of the study of Jufriadif Na'am et al [43] (2021) are in line with this finding of the present study in such a way that the results of their study showed that: before the start of general vaccination against COVID-19, most hospitalized patients had radiology results showing ground glass opacity (GGO) in their thorax.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the detection will be tested to measure the severity of the lung condition with the detected GGO object. The measurement process can be carried out using Equation 1 [20].…”
Section: Resultsmentioning
confidence: 99%
“…The problem in the GGO diagnosis process was initially carried out by presenting fairly good results with an accuracy of 90.83% and an average precision of 0.905 [19]. Furthermore, other studies have also explained that DIP is able to produce a model for identifying lung damage due to COVID-19 based on the description of the GGO pattern [20]. DIP can also be used as a useful tool for clinical practitioners and radiologists in the process of diagnosis, quantification, and follow-up in handling COVID-19 cases [21].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the image extraction process using the morphological method are then labeled for each matrix area using the Regionprops method. Regionprops detects white objects with a pixel value of 1 and black objects with a pixel value of 0 as the background [29].…”
Section: Regionprops Methodsmentioning
confidence: 99%